The knowledge, practice, and attitude regarding antibiotic use among attendants of primary health care centres: a cross-sectional study in Qatar - J. B. Alkhuzaei, Ameera Mohamedhayder; Salama, Rasha ElSayed; Eljak, Izz Eldin; Chehab, Mohamad Abdul Halim; Selim, Nagah Abdel Aziz (International Journal Of Community Medicine And Public Health, 2017)
Background: The inappropriate use of antibiotics is a significant global health problem as it is contributing to the development of antimicrobial resistance. Thus, this study aimed at assessing the knowledge, attitude, and practice of antibiotic use among patients attending primary health care (PHC) centres in Qatar. Methods: 722 adult patients from the primary health care centres were recruited and a self-administered questionnaire was employed. Results: Regarding the knowledge, 69.9% of patients believed that completing the full course of antibiotics is a necessity. In addition, more than half of the interviewees believed that antibiotics are necessary to treat a sore throat or an ear infection. Interestingly, regarding the practice, more than half (54.4%) of the interviewed patients often requested antibiotics as part of their treatment. Regarding the attitude, many patients (87.2%) pressured physicians to be given an antibiotic. Conclusions: This study revealed that patients often have inadequate knowledge about antibiotic use, which affects their attitude and practice. Thus, educating patients may reduce unnecessary antibiotic use and resistance in the community.